FILOSOFI ARSITEKTUR MASJID AL-MISHBAH:Studi Arsemiotika Ikon-Indeks-Simbol - Gunardi, Yudhi; Handayani, Sri; Permana, Asep Yudi; Widaningsih, Lilis (Jurnal Arsitektur ZONASI, 2021)
Abstract: Al-Mishbah Mosque is an architectural work with unique contemporary ideas and symbolic meaning requirements so that its existence is interesting to study. The researcher who is also the architect of the Al-Mishbah Mosque aims to examine the visually identified symbolic signs and describe the meaning of the architectural philosophy behind the design of the Al-Mishbah Mosque. This study uses a qualitative descriptive method and is analyzed using the theory of architectural semiotics (arsemiotics) to investigate signs which, according to Charles Sanders Peirce, are icons, indexes, and symbols. Based on the analysis of visually identified signs, the results of this study can be concluded that the signs and meanings of the architectural philosophy of the Al-Mishbah Mosque are as follows: (1) The black cube shape in the main building, is a symbolic idea of the Kaaba, which means as the center of the building. Qibla orientation of Muslim prayer, as well as a symbol of one direction and unity of Muslims. (2) The shape of the asymmetrical curved concrete hat is a symbolic idea of people prostrating, which means the main function as a mosque (a place of prostration), also has a meaning as a symbol of servitude to Allah. (3) The form of the text lafadz "Allah" on the facade of the upper building, is a symbolic idea of Baitullah, which means a place to glorify Allah, also means the mosque as "House of Allah". (4) The configuration of asymmetrical mass forms is a symbolic idea of Ijtihad, which means a genuine effort to find solutions to the problems of the people, also means not taking pre-existing general habits without understanding their essence (taqlid). (5) The shape of the mihrab wall with an open gap, from inside the mosque you will see the sky and the earth as a symbolic idea of the Kauniah verse which means that humans must see the verses of Allah have a balance between dhikr and thinking, also the existence of the universe and life is interpreted as evidence of existence almighty God. (6) The light that radiates out of the building resembles a person prostrating, is a symbolic idea of the light of prayer which means preventing heinous acts and evil deeds, and showing submission, obedience and obedience to Allah (taqwa).Keywords: Mosque Architecture, Semiotics, Arsemiotics, Symbolic Meaning, Al-Mishbah Mosque.Abstrak: Masjid Al-Mishbah merupakan suatu karya arsitektur dengan gagasan kontemporer yang unik dan syarat makna simbolik sehingga keberadaanya menarik untuk diteliti. Peneliti yang juga sekaligus arsitek Masjid Al-Mishbah bertujuan meneliti tanda-tanda simbolik yang teridentifikasi secara visual dan mendeskripsikan makna filosofi arsitektur dibalik rancangan Masjid Al-Mishbah. Penelitian ini menggunakan metode deskriptif kualitatif dan dianalisis menggunakan teori semiotika arsitektur (arsemiotik) untuk menyelidiki tanda yang menurut Charles Sanders Peirce, sebagai ikon, indeks, dan symbol. Berdasarkan analisis tanda-tanda yang teridentifikasi secara visual, hasil penelitian ini dapat disimpulkan bahwa tanda dan makna filosofi Arsitektur Masjid Al-Mishbah adalah sebagai berikut : (1) Bentuk kubus hitam pada bangunan utama, merupakan gagasan simbolik Kaâ€™bah, yang bermakna sebagai pusat orientasi qiblat shalat umat Islam, juga sebagai simbol satu kesatuan arah dan persatuan umatÂ  Islam.Â  (2) Bentuk topi beton lengkung asimetris merupakan gagasan simbolik orang bersujud, yang bermakna fungsi utama sebagai masjid (tempat bersujud), juga bermakna sebagai simbol penghambaan kepada Allah. (3) Bentuk teks lafadz â€œAllahâ€ pada fasad gedung bagian atas, merupakan gagasan simbolik Baitullah, yang bermakna tempat mengaggungkan Allah, juga bermakna masjid sebagai â€œRumah Allahâ€. (4) Konfigurasi bentuk massa asimetris merupakan gagasan simbolik Ijtihad, yang bermakna upaya sungguh-sungguh untuk mencari solusi permasalahan umat, juga bermakna tidak mengambil mentah-mentah kebiasaan umum yang sudah ada sebelumnya tanpa memahami makna esensinya (taqlid). (5) Bentuk dinding mihrab dengan celah terbuka, dari dalam masjid akan terlihat langit dan bumi sebagai gagasan simbolik Ayat Kauniah yang bermakna manusia harus melihat ayat-ayat Allah memiliki keseimbangan antar berdzikir dan berfikir, juga adanya alam semesta dan kehidupan dimaknai sebagai bukti ada dan mahakuasanya Allah. (6) Cahaya yang memancar keluar dari bangunan menyerupai orang sujud, merupakan gagasan simbolis cahaya shalat yang bermakna mencegah perbuatan keji dan munkar, serta menunjukan sikap tunduk, patuh dan taat kepada Allah (Taqwa).Kata Kunci: Arsitektur Masjid, Semiotika, Arsemiotik, Makna Simbolik, Masjid Al-Mishbah.